Sol-Gel Materials for Energy, Environment and Electronic Applications - Pillai, Suresh C.; Hehir, Sarah (Springer International Publishing : Imprint: Springer, 2017)
This volume provides expert coverage of the state-of-the-art in sol-gel materials for functional applications in energy, environment and electronics. The use of sol-gel technology has become a hotbed for cutting edge developments in many fields due to the accessibility of advanced materials through low energy processes. The book offers a broad view of this growing research area from basic science through high-level applications with the potential for commercialization and industrial use. Taking an integrated approach, expert chapters present a wide range of topics, from photocatalysts, solar cells and optics, to thin films and materials for energy storage and conversion, demonstrating the combined use of chemistry, physics, materials science and engineering in the search for solutions to some of the most challenging problems of our time. Offers a complete reference for sol-gel materials for functional applications Provides detailed coverage of a growing field Presents a wide range of applications, from photovoltaics and battery materials through coatings, materials for waste water treatment, microelectronics and ferroelectrics Represents essential reading for advanced undergraduate and graduate students, Ph.D. researchers, postdocs and academic and industry researchers working in the areas of materials science, engineering, chemistry and nanotechnology.
Keywords: Materials science.; Energy storage.; Inorganic chemistry.; Sustainable development.; Optical materials.; Electronic materials.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books